Bycatch Estimates From a Pacific Tuna Longline Fishery Provide a Baseline for Understanding the Long-Term Benefits of a Large, Blue Water Marine Sanctuary - Jaiteh, Vanessa; Peatman, Tom; Lindfield, Steve; Gilman, Eric; Nicol, Simon (Frontiers in Marine Science, 2021)
Bycatch on pelagic tuna longlines has contributed to population declines in several far-ranging, oceanic species and presents a conservation challenge that area-based management tools are increasingly promoted to address. In January 2020 the Republic of Palau, concerned about the impacts of longline fishing in its waters, closed 80% of its exclusive economic zone to all extractive activities, reserving the remaining 20% for a domestic fishing zone (DFZ). One of a growing number of very large marine protected areas, the Palau National Marine Sanctuary spans ~500,000 km2 and was established inter alia to allow for the recovery of fish stocks adversely impacted by tuna longline fleets. Given that the main tuna stocks targeted in the western Pacific are not overexploited, the benefits of protection potentially afforded by the sanctuary are likely greater for vulnerable bycatch species. Evaluations of the sanctuary’s performance require, in part, a baseline of historical catch rates and effort distribution in the distant-water (DWF) and locally-based (LBF) fleets operating in Palau prior to sanctuary implementation. We describe the fishing effort, catch rates, catch estimates and fishing mortality in Palau’s longline fishery based on logbook, observer and electronic monitoring data. Between 2010 and 2020, 104.8 million hooks were deployed, catching over 2 million individuals from 117 taxa at an overall target:bycatch ratio of 1:1, with a retention rate of ~62%. Pronounced differences in fishing strategies and spatial distribution of effort between fleets were associated with large variations in catch rates and composition. The LBF had a larger effect on populations of at-risk species relative to the DWF, with higher catch rates and magnitudes for several vulnerable species and higher observable fishing mortality rates. The sanctuary reshaped Palau’s longline fishery, contracting the fishery’s area and capacity. The relocation of the DFZ eliminated the LBF and constrained the DWF to an area where the fleet’s total catch rates and those of a number of vulnerable species were historically lower relative to fishing grounds now closed by the sanctuary. Our results highlight the importance of consistent bycatch monitoring and emphasise the need for regional area-based approaches for managing longline fisheries.